Three-dimensional speckle-tracking imaging for the prognosis of childhood-onset systemic lupus erythematosus: a pilot study - Feng, Xiaoyuan; Zhou, Ping; Ding, Yan; Peng, Jing; Wang, Tao (Frontiers in Pediatrics, 2025)
BackgroundTo assess the early alterations in the architecture and performance of the left ventricle for childhood-onset systemic lupus erythematosus (cSLE) patients utilizing three-dimensional speckle tracking imaging (3D-STI).MethodsThe aggregate of 31 cSLE patients were recruited and categorized into two groups based on the SLE disease activity index (SLEDAI) score: the mild-to-moderate group (≤12, n = 14) and the severe group (>12, n = 17). Univariate as well as multivariate logistic regression were used to investigate the relationship between 3D-STI parameters and the activity of the disease. Four diagnostic patterns were employed to amalgamate 3D-STI data (global longitudinal strain, GLS, and left ventricular twist angle, LVtw): isolation, series, parallel, and integration, subsequently leading to the development of a 3D myocardial comprehensive index (3D-MCI). The primary aim was severe disease activity, whereas the secondary objectives were growth failure, lupus nephritis, hypocomplementemia, and serious hematological issues.ResultsIn the multivariate analysis, GLS and LVtw emerged as significant indicators of severe disease activity (p = 0.028 and p = 0.047). The comprehensive method, which integrates GLS with LVtw value using the logistic algorithm, achieves a balanced sensitivity and specificity of 81.4% and 94.1%, respectively. Subsequently, the 3D-MCI is computed as follows: 7.650–0.367*GLS (%) - 0.281*LVtw (°). Furthermore, the 3D-MCI exhibited a strong significant correlation with both the primary endpoint and the secondary outcomes.Conclusions3D-STI technology may facilitate the early detection of cardiac injury in individuals with cSLE, whereas 3D-MCI serves as suitable prognostic indicators for cSLE patients.